Satellite-detected phytoplankton blooms in the Japan/East Sea during the past two decades: Magnitude and timing - Wang, Dingqi; Fang, Guohong; Jiang, Shumin; Xu, Qinzeng; Wang, Guanlin; Wei, Zexun; Wang, Yonggang; Xu, Tengfei (Frontiers in Marine Science, 2022)
The Japan/East Sea (JES) is known as a mid-latitude “Miniature Ocean” that features multiscale oceanic dynamical processes. Using principal component analysis (PCA), we investigate the variability of the sea surface chlorophyll-a concentration (SSC) and its bloom timing in the JES based on satellite remote sensing products spanning 1998–2019. The JES SSC exhibits strong seasonal variability and blooms twice annually. The spring bloom is induced under combined factors of increased photosynthetically active radiation (PAR), weakened wind speeds and sea ice melting, and terminated by the enhanced stratification. The fall bloom is induced by destratification and active dynamic processes (such as upwelling and front), and terminated by decreased PAR. The interannual variability of spring and fall bloom occur along the northwestern coast of the JES and in the deep Japan Basin, respectively. The positive SSC anomalies along the northwestern coast of the JES in spring is associated with more sea ice in the previous winter, weaker wind speed, and stronger stratification induced by the El Niño events. No significant relationship has been found between the fall bloom and the El Niño events. The bloom timing is controlled by the critical depth hypothesis. The initiation/termination timing of spring blooms has shifted earlier by 0.37/0.45 days, and the counterpart of fall blooms has shifted 0.49/1.28 days earlier per year. The duration and magnitude are independent with each other for spring bloom at interannual time scale. In contrast, they are positively correlated for fall bloom, because of both bloom timing and magnitude are dominated by active oceanic dynamical processes in fall.